Kinetic modeling of peroxydisulfate pre-treatment of algae slurry (Pasir Gudang, Malaysia) for increasing methane generation from anaerobic digestion : Fertilizer recovery - Siddique, Md. Nurul Islam; Zaied, Khalid; Mohd Zamri, Ibrahim; Wb, Wan Nik; Noraaini, Ali; Nazaitulshila, Rasit (Asian Publication Corporation, 2022)
This study looked into the possibility of using peroxydisulfate pretreatment to enhance biogas production from anaerobic fermentation of algal slurry. The results demonstrate that a peroxydisulfate added system with a dose of 0.02 g peroxydisulfate/g algal sludge TSS produces the most accumulative methane after 61 days of fermentation. At 0.02, 0.03, 0.06, 0.2, 0.3, 0.6, and 1.2 g peroxydisulfate/g algal sludge TSS cumulative methane generation was 1.16, 1.09, 1.15, 1.14, 1.09, 0.77, and 0.16 times higher than control. After 120 minutes of pre-treatment, the SCOD in the system continued to rise when the peroxydisulfate dosage was enhanced. To simulate the methane yield, a one-substrate model might be utilized. After dosing with peroxydisulfate, the hydrolysis rate reduced, and the maximum resultant and anticipated cumulative methane output was achieved with 0.02 g peroxydisulfate/g algal sludge TSS. After digestion, microcystin-LR in algae slurry was mostly eliminated. Heavy metals could be released from algae cells into the effluent as a result of the greater peroxydisulfate dosage. From the fermented effluent, sludge recapture was 0.09 m3 sludge/m3. The supplementation of peroxydisulfate to algae slurry may boost cumulative methane generation while also lowering microcystin-LR levels.